2014
DOI: 10.1016/j.hemonc.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The incidence rate of prostate cancer in Saudi Arabia

Abstract: There was a steady increase in the CIRs and ASIRs for prostate cancer between 2001 and 2008. The eastern region, Riyadh and Makkah had the highest overall ASIR in Saudi Arabia. Further effective screening programmes and active treatment measures are needed to control prostate cancer disease among Saudi men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…Prostate cancer is one of the major health problems in the world (1), has a significant impact on patients' and their caregivers' quality of life, and imposes heavy costs on them (2). It is the second most common cancer and the second leading cause of death from cancer among the male population worldwide (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer is one of the major health problems in the world (1), has a significant impact on patients' and their caregivers' quality of life, and imposes heavy costs on them (2). It is the second most common cancer and the second leading cause of death from cancer among the male population worldwide (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, there was significant relation between SPE and age (p<0.05). A recent study by Alghamidi et al in 2013 (18) showed that the incidence is higher than expected, with an age-standardized incidence rate of up to 10.1 in the eastern region. One further study by Al-Abdin et al (19) investigated the detection rate of prostate cancer in a cohort of Saudi men compared to their Canadian counterparts; it was evident from their report that there was a significantly low detection rate of prostate cancer in the Saudi group even with PSA values as high as 10 ng/mL, which suggested an increase in the threshold for taking a TRUS-guided biopsy.…”
Section: Discussionmentioning
confidence: 88%
“…The lowest incidence was in Asia and Africa. (1) The incidence of prostate cancer was reported to be about 74-127/100,000 men in the United States of America (USA) (2) , as compared to only 3, 10.2 and 14.5/100,000 men in Saudi Arabia (3) , Oman (4) and Kuwait (5) . In Egypt, cancer prostate is much less frequent than that of liver.…”
Section: Introductionmentioning
confidence: 99%